An Experimental and Numerical Study of Diorite-Porphyrites With Different Weathered Degree in the Direct Shear Test - Fan, Haotian; Sun, Shaorui; Le, Huilin; Zhu, Feng; Wang, Wuchao; Liu, Yong; Wang, Jin (Frontiers in Earth Science, 2020)
There are many well-developed weathered diorite-porphyrites, except main rocks, in Jurong pumped storage power station of Jiangsu province, China. Due to different geological environments, diorite-porphyrites are emerged by faults invading and can alter from weakly weathered to strongly weathered in less than half a year, which directly affected the safety and stability of hydraulic structures. Therefore, it is important to study the mechanical properties of diorite-porphyrites with different weathering degrees. The main purpose of this paper is to investigate the effects of different weathering degrees on the shear behavior and mechanical properties of diorite-porphyrites. Experimental and numerical direct shear tests were performed under normal stresses of 0.54MPa, 0.77MPa, 1.53MPa and 2.30MPa on strongly weathered, moderately weathered and weakly weathered samples, respectively. The test results show that with the increase of weathering degree, the chemical composition changed, the cohesion and internal friction angle both decreased. Crack initiation, propagation and coalescence were all observed with the numerical simulations using PFC2D. The numerical results are in good agreement with the experimental results and this numerical approach can reproduce the shear behavior of weathered diorite-porphyrites under different shear conditions. Based on the gradient of the pre-peak stage, peak stress and residual stress, the shear stress-displacement curves can be categorized into three types: type A (mostly for strongly weathered diorite-porphyrite), type B (mostly for moderately weathered diorite-porphyrite) and type C (mostly for weakly weathered diorite-porphyrite). A set of microparameters that can properly simulate the weathered diorite-porphyrites in PFC2D were proposed, which can be applied in the engineering simulation for further analysis.